Crystal structure of 1-[(Z)-[4-(4-methoxyphenyl) butan-2 ylidene]amino]-3-phenylurea, C18H21N3O2 - Tan, Ming Yueh; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Tiekink, Edward R.T. (Walter de Gruyter GmbH, 2018)
C18H21N3O2, triclinic, P1̅ (no. 2), a = 8.5155(4) Å, b = 10.6415(4) Å, c = 19.0732(10) Å, α = 80.918(4)°, β = 89.689(4)°, γ = 80.666(4)°, V = 1683.74(14) Å3, Z = 4, Rgt(F) = 0.055, wRref(F2) = 0.133, T = 100 K.